PEMBUATAN FILM DOKUMENTER “SENI ANYAMAN SUMBER KEHIDUPAN” DENGAN METODE CYCLIC STRATEGY - Muliati, Ethi; Noferianto Sitompul; Vanie Wijaya (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
ABSTRACT The community's life in Sambas has long been known for its handicrafts, specifically bamboo and rattan crafts, which boast unique diversities. The art of weaving bamboo and rattan has been a source of livelihood and an integral part of Malay culture that needs to be preserved. Therefore, media is required as a means of preservation, and one of the approaches is by creating a documentary film. This research aims to produce a documentary film as a cultural preservation medium. The making of this documentary film employs the cyclic strategy method and applies cinematography techniques in video recording.Based on the results of testing by two media experts, the film received a score of 90%, while two subject matter experts gave it a score of 88%. Furthermore, from 30 respondents, 91.73% expressed their strong agreement with the content, indicating that the documentary film is suitable for publication. It has a duration of 19 minutes and 22 seconds, with an H.264 1080p format, specifically MP4.